Harmonization of Narcotics Criminal Law: Reconstructing the Paradigm for Aligning Law No. 35 of 2009 with Law No. 1 of 2023 from the Perspective of the Lex Specialis Principle - Reyhand Parlindungan; Sumarno; Suci Ramadhani; Aries Kata Ginting; Daniel Naibaho (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
The enactment of Law No. 1 of 2023 concerning the National Criminal Code (KUHP) has initiated a fundamental shift in Indonesia’s criminal law doctrine, moving from a predominantly retributive and punitive paradigm toward a restorative and rehabilitative approach to justice. Nevertheless, narcotics-related offenses remain governed by Law No. 35 of 2009 on Narcotics, which occupies the position of a lex specialis systematica within the Indonesian legal system. This normative legal research aims to examine the urgency of juridical harmonization between these two legislative frameworks and to analyze the role of a legislative adjustment mechanism in eliminating normative dualism. Employing both a statutory approach and a conceptual approach, this study reveals that inconsistencies between the National Criminal Code and the Narcotics Law, particularly regarding mandatory minimum sentencing provisions and alternative penal mechanisms, have the potential to generate legal uncertainty (rechtsonzekerheid). Such normative discrepancies may create difficulties in the uniform application of criminal law and undermine the objectives of legal reform. Accordingly, this study argues that the reformulation of penal policy must be accommodated through a comprehensive adjustment statute designed to harmonize the relationship between the National Criminal Code and the Narcotics Law. Such harmonization is essential to ensuring proportionality in sentencing, particularly by differentiating between perpetrators involved in illicit narcotics trafficking as part of organized criminal networks and narcotics users who should be regarded primarily as victims of substance abuse requiring rehabilitation and restorative intervention